Parametric investigation on the erosion characteristics of hydrodynamic cavitation abrasive finishing process - Tay, Zhi Ming (Nanyang Technological University, 2020)
Hydrodynamic cavitation abrasive finishing (HCAF) has recently been introduced as a novel surface finishing technique aimed at achieving superior surface finishing quality in external channels of additively manufactured (AM) components. It has shown to be effective at removing surface irregularities from AM components by combining the effects of the high material rate of removal (MRR) in cavitation erosion and fine-finishing quality in abrasive finishing. This thesis aims to investigate the effects of HCAF on the surface finishing quality (material removal, surface roughness and surface topography images) of AM specimens, and recommend suitable surface finishing parameters based on the effects of HCAF. A parametric investigation was conducted by varying parameters of cavitation upstream pressure (Pu1), abrasive upstream pressure (Pu2), abrasive size (As), abrasive concentration (Ac), and processing time. The study showed that experiments with a combination of low Pu1, Pu2, As and Ac did not significantly improve surface roughness. Besides, experiments with high Pu1 of 250 bars resulted in crater-like depressions on the specimens, thus high Pu1 should not be used for surface finishing purposes. Also, As dominates Ac in terms of material removal and Pu2 dominates As and Ac in terms of surface roughness when high Pu2 of 10.0 bar is used. This suggests that lower Ac may be used to achieve a similar finishing effect and reduce abrasive consumption. Furthermore, As dominates Pu2 in terms of surface roughness when high As of 50 μm is used. This suggests that lower Pu2 may be used to achieve a similar finishing effect and reduce energy consumption. Furthermore, the processing time in some experiments may be reduced by half as surface roughness did not improve significantly with processing time. Lastly, the best surface finishing quality is found with low Pu1 and high Pu2, As and Ac. Specifically, the parameters of the experiment are Pu1 = 50 bar, Pu2 = 10.0 bar, As = 50 μm and Ac = 1.0 %.